English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

this is solving quadratic equations by factoring.

2006-12-03 13:06:07 · 12 answers · asked by vballprep22 1 in Science & Mathematics Mathematics

12 answers

t = 0.5 and -3

2006-12-03 13:08:50 · answer #1 · answered by Rajkiran 3 · 0 0

Ok: 2(t^2) + 5t -3 = 0

Since we are told that we can solve this by factoring we should be able to rewrite this as:

(at+b)(bt+d)=0

Just to point something out, you may not always be able to do this! Sometimes you cannot factor quadratic equations! In that case you need the quadratic formula to find the roots, which you can easily find by searching quadratic formula on the Internet.

So: (at+b)(ct+d)=ac(t^2) +(ad+bc)t +bd
ac=2, (ad+bc)=5 , and bd=-3

let's make a=1, c=2
(d+2b)=5 and bd=-3 so b=3, d=-1

So, putting the values for a,b,c, and d we have (t+3)(2t-1)=0

check: (t+3)(2t-1)=2t^2 -t +6t -3=2t^2 +5t -3, so we are right.

The roots for (t+3)(2t-1)=0 are t=-3 and t=1/2

2006-12-03 13:27:13 · answer #2 · answered by William M 2 · 0 0

Since the lead coefficient is 2 the only factors are 1 and 2, the only factors of the constant term are 1, and 3, and since the sign of the constant teerm is negative, look for the factors of 6 that differ by 5.

(2x – 1)(x +3) = 0

Now, by the zero product rule either 2x – 1 = 0 or x + 3 = 0, hence the two solutions are

x = 1/2 or x = –3

2006-12-03 13:11:33 · answer #3 · answered by Dennis T 1 · 0 0

let us split 5 into 2 numbers product -6 ( 2* (-3)

5 = 6 -1

now 2t^2+5t- 3
= 2t^2+6t-t-3
= 2t(t+3)-(t+3)
= (2t-1)(t+3)
= 0
means t = 1/2 or t = -3

the above 2 are solutions
I hope I helped

2006-12-03 13:09:47 · answer #4 · answered by Mein Hoon Na 7 · 0 0

(2t+1)(t-3)=0 which means that t= -1/2 , t= 3

2006-12-03 13:09:28 · answer #5 · answered by Anonymous · 0 0

2t^2 + 5t - 3 = 0

(2t -1) (t+3) = 0

2006-12-03 13:08:04 · answer #6 · answered by dst3313 3 · 0 0

(2t - 1)(t + 3) = 0

so 2t -1 = 0 or t + 3 =0

2t - 1 = 0
2t = 1
t = 1/2

t + 3 = 0
t = -3

t = 1/2 or -3

2006-12-03 13:07:33 · answer #7 · answered by disposable_hero_too 6 · 0 0

use quadratic equation -b+- sqrt b^2-4(ac)/2a

-5+- sqrt 49/2(2)
-5+-7/4
-5+7/4=1/2
-5-7/4=-3
Your two answers are 1/2 and -3

2006-12-03 13:19:32 · answer #8 · answered by celticevening 1 · 0 0

remember this formula [-b+-sqrt(b^2 - 4ac)]/2a for more complicated equations a=2 b=5 c= -3

2006-12-03 13:18:45 · answer #9 · answered by Wasabi 3 · 0 0

(2t- 1)(t+3)

2006-12-03 13:08:27 · answer #10 · answered by Anonymous · 0 0

i combined the termes and i got7t to the power3= -3

2006-12-03 13:09:42 · answer #11 · answered by idkjustanothergurl 3 · 0 0

fedest.com, questions and answers